Toward a More Sustainable Democracy: Public Participation in Justice Sector Reform - Mcilvain, Ashley (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: In both researching and participating in the process of planning and implementing rule of law reforms, I saw several trends that seemed to indicate a need for change. It is these themes that have guided the development of this paper and my hopes of its application in future rule of law promotion efforts. The experience of donors and practitioners in countries around the world in recent years has illustrated that: Reforms led by international donors do not always coincide with local priorities or needs; Institutional reforms often unravel after the international community's departure due to a lack of domestic capacity or support; The broader public is often excluded from and disillusioned with the reform process; Reforms do not always adequately address the need to develop a participatory tradition or the existing public cynicism about democratic participation in government. Certainly, these are themes already raised by a wide range of scholars and practitioners. Current wisdom now dictates that: Development of both the process and content of reforms should include local input and be subject to local control; Local capacity-building should be a priority in the reform process from the outset; Civic education is a necessary antecedent to effective democratic participation; The reform process itself is equally as important as its final product in determining the legitimacy of the institutions it creates. Even among those that agree with these points, the question remains as to how these goals can be most effectively accomplished. The research and program analysis I present here examines how public participation in rule of law reform may complement existing initiatives to help achieve these goals. Such an approach is certainly not immune to critique. Many international donors, state governments and publics alike are skeptical about either the value or efficacy of public participation in government reform and work, not least because it remains a new field of exploration with little empirical evidence to support it. There is, however, much anecdotal evidence of state and local reforms of the police and judiciary where public involvement was a key component in building public trust in the reform process and the government, increasing the legitimacy of the police and judiciary, and improving the accountability and effectiveness of these institutions. Through the analysis and examples included in this study, I have attempted to provide an objective assessment of the potential benefits and drawbacks of a participatory approach, raising issues relevant to international and state actors considering whether to integrate public participation in their particular reforms. I have also sought to address how civic education and gradual public engagement may be used to reduce public cynicism and reticence toward democratic participation. In vetting the rationale, opportunities and practical challenges to such participation, it is my hope that the initiatives discussed here may be successfully integrated into current and future reform programs to provide a more holistic approach to rule of law promotion in new democracies.